Law 10639/2003: thoughts on the afro-brazilian culture and the usage of imagery in school and educational processes (Research, Society and Development, 2021)
This paper aims to discuss the fulfillment of law 10.639/03, which commands in basic education the formation of students’ consciousness regarding the historical processes that portray the presence of black people in Brazil’s history and their contribution to the formation the country’s national identity, which has been historically neglected in teaching materials such as textbooks/didactic books. Therefore, through a bibliographic and documentary research, we intend to affirm that, since the Colonial Period, black people’s contribution has been pivotal in building cultural identity and towards the development of our country and our people. As learning tools, we shall discuss the usage of imagery, as they can be used by teachers in a daily basis, so as to enhance the history and the culture, tearing down prejudices and discriminations that are still deeply rooted in our society, something that ends up minimizing historical paths, social roles and black people’s contribution to our nation.